Gestão por processos de negócios em uma empresa de pesquisa e desenvolvimento - Sentanin, Odemilson Fernando; Santos, Fernando César Almada (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper aims at analyzing the implementation and the evolutive stage of the business process management inthe Farming and Cattle Raising Instrumentation, one of EMBRAPA’s (Brazilian Agricultural Research Corporation)40 research and development centers. It is analyzed – theoretically and practically – the relationship amongthe business processes and the business strategy, the organizational changes and the evolutive stages of the organizationstowards business process management. Once a certain organization is aware of its current evolutive stage,it is able to plan changes at strategic and organizational levels. The case study was performed by means of analysisof documents and reports, interviews with enterprise managers and employees and the participation of the firstauthor of this paper in the planning and implementation of the business process management at the research anddevelopment center investigated. The studied organization is at an intermediate evolutive stage towards businessprocess management. Any resistance to this new management model is being reduced by incorporating the conceptsand further knowledge on the approach of processes by executives and employees. The depth of the performedanalysis on the case study will allow for more structured research in a wider set of samples of enterprises.Keywords: Business process management; Business strategy; Strategic planning; Organizational structure; Organizationalchange; Evolutive stages.